The Effectiveness of Learning to Read Al-Qur'an Al-Husna Method at Pondok Tarbiyatul Qur'an (PTQ) Cahaya Nusantara Dukuh Jetak, Wonorejo Village, Gondangrejo District, Karanganyar Regency - Setyawan, Agus; Rohimah, Siti (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
Reading the Qur'an is a must for Muslim ummas. However, it is unfortunate that 65 percent of Indonesia's population cannot read the Koran. Illiteracy of the Qur'an must be eradicated immediately, and this is our shared responsibility. One way to eradicate Al-Qur'an illiteracy is to teach students as early as possible. The purpose of this study was to determine the effectiveness of learning to read the Koran using the Al-Husna method for class 1 students at Pondok Tarbiyatul Qur'an Karang Anyar. This study uses descriptive quantitative research methods, so the results obtained are decomposed data. Data collection is done by observation, interviews, documentation, journals and newspapers. The results of the study showed that learning to read the Koran using the Al-Husna method was effective in improving the ability to read the Koran for grade 1 students at Pondok Tarbiyatul Qur'an Cahaya Nusantara Jetak, Wonorejo, Gondangrejo, Karang Anyar. Students totaling 21 students completed completing the Al-Husna learning method within 3 to 4 months and were able to read the Al-Qur'an. The story and saying method approach increases the participants' activeness, interest and motivation. In addition, there are factors that support the effectiveness of learning to read the Qur'an using the Al-Husna method, namely, the sincerity of students in learning and teachers in teaching, increasing flight hours, concentration, applying learning designated by the al-Husna method (maintain adab), competent teachers, adequate facilities and infrastructure, cooperation between teachers and parents, and always pray to get useful knowledge. This method can be a valuable alternative in increasing the effectiveness of learning to read the Koran in Al-Qur'an educational institutions.